Influence of Hydraulic Retention Time (HRT) upon the Treatment of Wastewater by a Laboratory-Scale Membrane Bioreactor (MBR) - Sozudogru, Onur; Massara, Theoni Maria; Calik, Savas; Yilmaz, Alper Erdem; Bakirdere, Sezgin; Katsou, Evina; Komesli, Okan Tarik (TAYLOR & FRANCIS INC, 2020)
The effect of applying different hydraulic retention times (HRTs) was investigated for a lab-scale membrane bioreactor (MBR) treating domestic wastewater. The submerged flat-type ultrafiltration MBR was operated under three HRTs (576 min, 462 min, and 372 min) corresponding to three operating periods to investigate its efficiency in removing organic content and nutrients from domestic wastewater. The chemical oxygen demand (COD) decreased from 99 to 96.5% with the HRT decreased from 576 min to 462 min. The bacteria performing nitrification were affected by the HRT change: the ammonium (NH4-N) removal dropped from 98.5% (HRT of 576 min) to 74.2% (HRT of 462 min). With the HRT adjusted to the lowest value of 372 min, the COD and NH4-N removals were 94.4% and 55.8%, respectively. The phosphate (PO4-P) removal was 59.1%, 34.4%, and 28% during periods 1, 2 and 3, respectively. In terms of the COD removal efficiency, the treated effluent met the Turkish limits for discharge to the receiving water during all of the operating periods. The system performance was suitable in terms of NH4-N removal for periods 1 (HRT of 576 min) and 2 (HRT of 462 min). However, applying the operating conditions of period 2 (i.e., maintaining the HRT at 462 min) requires additional post-treatment (e.g., low-cost chemical precipitation) to enhance the PO4-P removal.
Keywords: Ammonium; hydraulic retention time; membrane bioreactor; membrane flux; organic content; phosphates; OIL MILL EFFLUENT; NUTRIENT REMOVAL; REACTOR; Chemistry